2009
DOI: 10.1080/10236660802506424
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Amphiphilic (Maleanilic acid-ran-styrene) Copolymers: Structural and Kinetic Properties

Abstract: A series of amphiphilic (maleanilic acid-ran-styrene) copolymers composed of hydrophobic and hydrophilic moieties were prepared by radical copolymerization using different molar feed ratios of maleanilic acid and styrene. The obtained copolymers were structurally examined by FT-IR, TGA, XRD, and SEM. The weight average molecular weight (M w ) was determined by light scattering method in DMSO and found to lie in the range of 20,000-334,000 g=mol depending upon the molar feed ratio of the maleanilic acid and sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The synthesis and structural characterization of poly(S-co-MA) copolymer backbone have been described in detail elsewhere [51]. Kinetic and thermal studies of this copolymer showed that the constituting styrene and maleanilic acid monomers are randomly arranged in the copolymer backbone.…”
Section: Synthesis and Structurementioning
confidence: 99%
“…The synthesis and structural characterization of poly(S-co-MA) copolymer backbone have been described in detail elsewhere [51]. Kinetic and thermal studies of this copolymer showed that the constituting styrene and maleanilic acid monomers are randomly arranged in the copolymer backbone.…”
Section: Synthesis and Structurementioning
confidence: 99%